Multiscale Theoretical Calculations Empower Robust Electric Double Layer Toward Highly Reversible Zinc Anode - Xia, Yufan; Luo, Zhen; Chen, Shuang; Xiang, Yang; Weng, Gao; Pan, Hongge; Xu, Ben Bin; Yan, Mi; Jiang, Yinzhu (Nano-Micro Letters, 2025)
The electric double layer (EDL) at the electrochemical interface is crucial for ion transport, charge transfer, and surface reactions in aqueous rechargeable zinc batteries (ARZBs). However, Zn anodes routinely encounter persistent dendrite growth and parasitic reactions, driven by the inhomogeneous charge distribution and water-dominated environment within the EDL. Compounding this, classical EDL theory, rooted in mean-field approximations, further fails to resolve molecular-scale interfacial dynamics under battery-operating conditions, limiting mechanistic insights. Herein, we established a multiscale theoretical calculation framework from single molecular characteristics to interfacial ion distribution, revealing the EDL’s structure and interactions between different ions and molecules, which helps us understand the parasitic processes in depth. Simulations demonstrate that water dipole and sulfate ion adsorption at the inner Helmholtz plane drives severe hydrogen evolution and by-product formation. Guided by these insights, we engineered a “water-poor and anion-expelled” EDL using 4,1’,6’-trichlorogalactosucrose (TGS) as an electrolyte additive. As a result, Zn||Zn symmetric cells with TGS exhibited stable cycling for over 4700 h under a current density of 1 mA cm−2, while NaV3O8·1.5H2O-based full cells kept 90.4% of the initial specific capacity after 800 cycles at 5 A g−1. This work highlights the power of multiscale theoretical frameworks to unravel EDL complexities and guide high-performance ARZB design through integrated theory-experiment approaches. Highlights: 1 A multiscale theoretical framework deciphers the molecular-ionic dynamics of the electric double layer (EDL) in aqueous rechargeable zinc batteries, correlating interfacial water aggregation, anion-specific adsorption, and electric field inhomogeneity to parasitic reactions and dendrite growth, thereby establishing EDL-driven design principles for ultra-stable Zn anodes. 2 Molecular adsorption engineering creates a localized “water-poor and anion-expelled” EDL configuration that suppresses hydrogen evolution and by-product formation while enabling dense Zn electrodeposition through flattened interfacial potential gradients and reduced Zn2+ electrostatic repulsion.